The Key Factors of Economic Integration in Southeast Asia: Case of Indonesia, Malaysia, and Thailand - Verico, Kiki (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2016)
Shifting from intra-regional trade to that of investment is the major aim of the economic integration of Southeast Asia. This article attempts to analyse the two essential factors of it, one is intra-regional trade and two is economic community. For the first analysis it selects Indonesia, Malaysia and Thailand as the observed countries and for the second analysis it takes Indonesia as the field study. Firstly, this article finds that free trade agreement is effective to increases intra-regional trade but ineffective to attract investment therefore Southeast Asia needs to amplify its open-regionalism principle. Secondly, it finds that private sector is ready towards the economic community therefore the ASEAN Economic Community is fit for the recent Southeast Asia’s integration.